A hard carbon material with a lamellar structure
Through chitin carbonization treatment and resin pore coating, a high-first-effect sheet-structure hard carbon material was prepared, which solved the problems of lithium-ion battery structure limitation and sodium-ion battery material improvement, and achieved high capacity and high cycle stability electrochemical properties.
Patent Information
- Application Number
- CN202411165174.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-23
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-08-23
AI Technical Summary
The cycling performance and rate performance of existing lithium-ion batteries are limited by the graphite negative electrode structural characteristics, and sodium-ion batteries require negative electrode materials with high specific capacity to reduce costs. The first effect of two-dimensional hard carbon materials is relatively low, making it difficult to meet the demand.
Using chitin as the precursor, hard carbon material with a sheet structure is prepared by carbonization treatment and resin pore coating, which improves its conductivity and active area and forms a closed-cell structure to enhance the adsorption and migration stability of sodium ions. sex.
Hard carbon materials with high first-term efficiency, high capacity and high cycle stability are achieved, the electrochemical performance and charge transfer efficiency of sodium ion batteries are improved, the side reaction between the electrolyte and the hard carbon surface is reduced, and the overall performance of the battery is improved. .
Smart Images

Figure CN118825241B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a hard carbon material with a lamellar structure. Background Art
[0002] At present, lithium-ion batteries are widely used in 3C consumer electronics, new energy electric vehicles, and renewable energy storage. Limited lithium resources, unbalanced distribution, and high costs are not conducive to its large-scale application in the field of energy storage. At the same time, the structural characteristics of commercial lithium-ion battery graphite negative electrodes hinder the further improvement of cycle performance and rate performance. Sodium-ion batteries have a similar energy storage mechanism to lithium-ion batteries. Due to their advantages of abundant resources and low cost, they are expected to replace lithium-ion battery products.
[0003] In order to further reduce the cost of sodium-ion batteries, it is necessary to find negative electrode materials with high specific capacity. Hard carbon is a disordered structural carbon with randomly oriented graphite domains, higher carbon layer spacing and some residual heteroatoms (mainly oxygen functional groups). It can provide more sodium ion diffusion paths and sodium ion storage sites, and is the best choice for the negative electrode of sodium-ion batteries. Two-dimensional (2D) hard carbon materials present a thin layer structure with infinite plane length, which is conducive to the adsorption of Na ions, increases the contact area between the electrode and the electrolyte, and can effectively reduce the diffusion distance of Na ions. However, the first efficiency (first coulomb efficiency) of two-dimensional (2D) hard carbon materials is low. Therefore, constructing a new type of high first efficiency new lamellar structure hard carbon is the primary task of two-dimensional (2D) hard carbon materials. Summary of the invention
[0004] In view of this, the present invention provides a hard carbon material with a lamellar structure. The hard carbon material has the advantage of high first efficiency.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] In a first aspect, the present invention provides a hard carbon material having a lamellar structure, the hard carbon material comprising a hard carbon matrix and a carbon layer coated on the surface of the hard carbon matrix;
[0007] The hard carbon matrix includes a chitosan-based hard carbon material. The chitosan-based hard carbon material has a stacked layer structure and a closed-pore structure.
[0008] Preferably, the closed porosity of the hard carbon material is 5% to 30%.
[0009] Preferably, the number of layers of the lamellar structure is ≥2.
[0010] In an embodiment of the present invention, the number of closed-cell structures is ≥1.
[0011] Preferably, the pore size of the closed-pore structure is 0.1 to 3 nm.
[0012] Preferably, the specific surface area of the hard carbon material is 8 to 15 m 2 / g.
[0013] Preferably, the thickness of the carbon layer is 2-5 nm.
[0014] Preferably, the particle size of the hard carbon material is 5 to 10 μm.
[0015] In a second aspect, the present invention provides a method for preparing the hard carbon material, comprising the following steps:
[0016] S1, in an inert gas atmosphere, performing a first carbonization treatment on chitosan, and obtaining a first product after a first ball milling treatment;
[0017] S2, mixing the first product and the cured resin to obtain a mixture;
[0018] In an inert gas atmosphere, subjecting the mixture to a second carbonization treatment to obtain a second product;
[0019] S3, sieving the second product to obtain a third product;
[0020] The third product is acid-washed and subjected to a second ball-milling treatment to obtain a hard carbon material.
[0021] Preferably, in step S1, the heating temperature of the first carbonization treatment is 500-900°C, and the holding time is 1-10 h.
[0022] Preferably, the heating rate of the first carbonization treatment is 0.1-10°C / min.
[0023] Preferably, in step S2, the curing degree of the cured resin is not less than 95%, the particle size is not less than 2 mm, and the carbon fixation rate is not less than 40%.
[0024] Preferably, the mass ratio of the first product to the cured resin is 1:(0.25-3).
[0025] Preferably, the mass ratio of the first product to the cured resin is 1:(0.5-2).
[0026] Preferably, in step S2, the heating temperature of the second carbonization treatment is 1200-1500°C, and the holding time is 1-10 hours.
[0027] Preferably, the heating rate of the second carbonization treatment is 0.1-10°C / min.
[0028] In a third aspect, the present invention provides a negative electrode plate, which includes the hard carbon material mentioned above, and / or the hard carbon material prepared by the above preparation method.
[0029] In a fourth aspect, the present invention provides a sodium ion battery comprising the above-mentioned negative electrode plate.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] The present invention uses chitosan as a precursor and the cured resin as a pore-forming agent and a coating agent, and can obtain a high-efficiency novel lamellar structure hard carbon material through simple pyrolysis and screening.
[0032] On the one hand, chitin is a natural linear polymer compound composed of N-acetyl-2-amino-D-glucose unit structures connected by β-1,4 glycosidic bonds. It has a large amount of nitrogen (N), which can not only improve the conductivity of carbon materials, but also increase the reactive sites of carbon materials with sodium ions, so that they can obtain excellent electrochemical properties. On the other hand, chitin presents a natural lamellar structure. The two-dimensional (2D) hard carbon material obtained after carbonization of chitin presents a distinct lamellar structure, which is interwoven by chitin nanofibers. This is not only conducive to the adsorption of Na ions, but also has little structural change during the charge and discharge process of sodium insertion and removal, which is conducive to Na + The stability of migration increases the contact area between the electrode and the electrolyte, which can effectively reduce the diffusion distance of Na ions. Therefore, chitosan carbon has the advantages of high conductivity, large active area and low contact resistance, which can achieve efficient charge transfer, thus having high capacity and high cycle stability.
[0033] At the same time, the cured resin (curing degree is not less than 95%) will produce CO, CO2 and alkane gases during the carbonization process. Among them, CO and CO2 have pore-forming functions, which make the chitosan-based hard carbon material produce an open-pore structure. As the carbonization proceeds, the chitosan-based hard carbon material undergoes C rearrangement and a closed-pore structure, which can increase the graphitization degree of the chitosan-based hard carbon material, thereby increasing the capacity of the chitosan-based hard carbon material. The generated alkane gases can be deposited on the surface of the chitosan-based hard carbon material to form a carbon layer, thereby reducing the specific surface area of the hard carbon material, reducing the side reactions between the electrolyte and the hard carbon surface, and effectively improving the initial effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is a scanning electron microscope image of the lamellar structure hard carbon material prepared in Example 1.
[0035] Figure 2 This is a scanning electron microscope image (surface layer) of the lamellar structure hard carbon material prepared in Example 1.
[0036] Figure 3 This is the HRTEM (transmission electron microscope) image of the lamellar structure hard carbon material prepared in Example 1.
[0037] Figure 4 This is the lamellar structure hard carbon material prepared in Comparative Example 1. DETAILED DESCRIPTION
[0038] The present invention discloses a hard carbon material with a lamellar structure. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve it. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art, and they are all considered to be included in the present invention. The method and application of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the methods and applications described herein without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention.
[0039] In the description of the present invention, it should be noted that the terms "first", "second", etc. are only used for descriptive purposes, and do not indicate or imply relative importance.
[0040] In the description of the present invention, a list of items connected by the term "at least one of" or other similar terms may mean any combination of the listed items. For example, if items A, B are listed, the phrase "at least one of A, B" means only A; only B; or A and B. In another example, if items A, B, C are listed, the phrase "at least one of A, B, C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.
[0041] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range or the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0042] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0043] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0044] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0045] Specifically, the present invention adopts the following technical solutions:
[0046] In a first aspect, the present invention provides a hard carbon material, which includes a hard carbon matrix and a carbon layer coated on the surface of the hard carbon matrix;
[0047] The hard carbon matrix includes a chitosan-based hard carbon material. The chitosan-based hard carbon material has a stacked layer structure and a closed-pore structure.
[0048] Preferably, the closed porosity of the hard carbon material is 5% to 30%. Exemplarily, the closed porosity of the hard carbon material is any value among 5%, 6%, 8%, 10%, 12%, 14%, 15%, 16%, 18%, 20%, 22%, 24%, 25%, 26%, 28%, 30%, or any value within the range of any two of the above values. Preferably, the closed porosity of the hard carbon material is 12% to 18%. If the closed porosity is too large, the compaction density of the material will be reduced, resulting in a decrease in the energy density of the material; if the closed porosity is too small, the material's specific capacity will be poorly utilized, and there will not be enough sodium storage area, resulting in a decrease in the energy density of the material.
[0049] Preferably, the number of layers of the lamella structure is ≥ 2. Exemplarily, the number of layers of the lamella structure is any value among 2, 5, 10, 20, 30, 40, 50, 60, 70, 80, 90, 100, 500, or any value within the range consisting of any two of the above values.
[0050] In an embodiment of the present invention, the number of closed-cell structures is ≥ 1. Exemplarily, the number of closed-cell structures is any value among 1, 2, 5, 10, 20, 30, 40, 50, 60, 70, 80, 90, 100, 200, 500, or any value within the range consisting of any two of the above values.
[0051] Preferably, the pore size of the closed-cell structure is 0.1-3 nm. Exemplarily, the pore size of the closed-cell structure is 0.1 nm, 0.2 nm, 0.4 nm, 0.5 nm, 0.6 nm, 0.8 nm, 1.0 nm, 1.2 nm, 1.4 nm, 1.5 nm, 1.6 nm, 1.8 nm, 1.9 nm, 2.0 nm, 2.2 nm, 2.4 nm, 2.5 nm, 2.6 nm, 2.8 nm, 3 nm, or any value in the range of any two of the above values. Preferably, the pore size of the closed-cell structure is 1.2-1.9 nm. When the pore size is greater than 3 nm, the gram capacity of the material can be further improved, but the cycle stability will be greatly reduced, resulting in a shorter battery life; when the pore size is less than 0.1 nm, there is almost no sufficient sodium storage pore size, which reduces the gram capacity of the material. When the material is between 0.1 and 3 nm, the gram capacity and the long cycle life of the battery can be taken into account to ensure the stability of the material.
[0052] Preferably, the specific surface area of the hard carbon material is 8 to 15 m 2 / g. Exemplarily, the specific surface area of the hard carbon material is 8 m 2 / g, 9 m 2 / g, 10 m 2 / g, 11 m 2 / g, 12 m 2 / g, 13 m 2 / g, 14 m 2 / g, 15 m 2 / g or any value in the range of any two of the above values. If the specific surface area of the hard carbon material is too large, a large number of SEI films will be generated during the first cycle of charge and discharge. This behavior will consume too much electrolyte and reduce the first cycle coulomb efficiency; if the specific surface area of the hard carbon material is too small, the electrolyte has poor wetting effect on the hard carbon material, which affects the high-rate cycle of charge and discharge. The specific surface area of the hard carbon material is between 8 and 15 m 2 / g range, which can effectively make the electrolyte infiltrate the material while ensuring high initial efficiency.
[0053] Preferably, the thickness of the carbon layer is 2 to 5 nm. Exemplarily, the thickness of the carbon layer is any value among 2 nm, 2.5 nm, 3 nm, 3.5 nm, 4 nm, 4.5 nm, 5 nm, or any value within the range of any two of the above values. If the carbon layer is too thick, the diffusion kinetics of the material will decrease, resulting in deterioration of the rate performance; if the carbon layer is too thin, the structural stability of the material will decrease, affecting the long cycle life of the material.
[0054] Preferably, the particle size of the hard carbon material is 5-10 μm. Exemplarily, the particle size of the hard carbon material is any value among 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, or any value within the range consisting of any two of the above values.
[0055] In a second aspect, the present invention provides a method for preparing the hard carbon material, comprising the following steps:
[0056] S1, in an inert gas atmosphere, performing a first carbonization treatment on chitosan, and obtaining a first product after a first ball milling treatment;
[0057] S2, mixing the first product and the cured resin to obtain a mixture;
[0058] In an inert gas atmosphere, subjecting the mixture to a second carbonization treatment to obtain a second product;
[0059] S3, sieving the second product to obtain a third product;
[0060] The third product is acid-washed and subjected to a second ball-milling treatment to obtain a hard carbon material.
[0061] In the embodiment of the present invention, the main source of chitosan raw materials is crab shells, so there may be certain protein and calcium carbonate impurities in the raw materials. When there are protein and calcium carbonate impurities in the chitosan raw materials, a pretreatment step of chitosan is also included before step S1 to remove protein and calcium carbonate impurities.
[0062] In the embodiment of the present invention, the pretreatment step of chitosan is: alkali washing and acid washing the chitosan, and drying the chitosan to obtain pretreated chitosan.
[0063] In an embodiment of the present invention, the alkaline washing in the pretreatment step is: placing chitosan in an alkaline solution with a mass percentage of 1% to 20%, stirring at a temperature of 50 to 70°C for 5 to 7 hours, filtering, and washing with water until neutral. The alkaline solution is, for example, a sodium hydroxide solution or a potassium hydroxide solution. The amount ratio of chitosan to the alkaline solution is (10 to 50) g: (100 to 500) mL.
[0064] In an embodiment of the present invention, the acid washing in the pretreatment step is: placing chitosan in an acid solution with a molar concentration of 0.5 to 2M, stirring at a temperature of 10 to 30°C for 10 to 14 hours, filtering, and washing with water until neutral. The acid solution is, for example, one or more of a hydrochloric acid solution, a nitric acid solution, and a sulfuric acid solution. The amount ratio of chitosan to the acid solution is (10 to 50) g: (100 to 500) mL.
[0065] Preferably, in step S1, the heating temperature of the first carbonization treatment is 500-900°C, and the holding time is 1-10 h. Exemplarily, the heating temperature of the first carbonization treatment is any one of 500°C, 600°C, 700°C, 800°C, and 900°C, or any value within the range of any two of the above values. Exemplarily, the holding time of the first carbonization treatment is any one of 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, and 10h, or any value within the range of any two of the above values.
[0066] Preferably, the heating rate of the first carbonization treatment is 0.1-10°C / min. Exemplarily, the heating rate of the first carbonization treatment is any value among 0.1°C / min, 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min or any value within the range of any two of the above values.
[0067] In an embodiment of the present invention, in step S1 or S2, the inert gas includes one or more of argon, helium, and nitrogen.
[0068] In an embodiment of the present invention, the gas flow rate of the inert gas is 50 to 70 mL / min. Exemplarily, the gas flow rate of the inert gas is any value among 50 mL / min, 55 mL / min, 60 mL / min, 65 mL / min, 70 mL / min, or any value within the range of any two of the above values.
[0069] In an embodiment of the present invention, the particle size of the first product is less than 45 μm.
[0070] Preferably, in step S2, the curing degree of the cured resin is not less than 95%, the particle size is not less than 2 mm, and the carbon fixation rate is not less than 40%. Exemplarily, the curing degree of the cured resin is any value among 95%, 96%, 97%, 98%, 99%, 100%, or any value within the range of any two of the above values, the particle size of the cured resin is any value among 2 mm, 5 mm, 10 mm, 15 mm, 20 mm, 25 mm, 30 mm, 50 mm, or any value within the range of any two of the above values, and the carbon fixation rate of the cured resin is any value among 40%, 50%, 60%, 70%, 80%, 90%, 100%, or any value within the range of any two of the above values.
[0071] In an embodiment of the present invention, the method for preparing the cured resin is: mixing the liquid resin with the curing agent, and curing at 140 to 160° C. for 1 to 3 hours.
[0072] In an embodiment of the present invention, the liquid resin includes at least one of phenolic resin, furfural resin and urea-formaldehyde resin.
[0073] Preferably, the mass ratio of the first product to the cured resin is 1:(0.25-3). Exemplarily, the mass ratio of the first product to the cured resin is any value among 1:0.25, 1:0.5, 1:1, 1:1.5, 1:2, 1:2.5, 1:3, or any value within the range of any two of the above values.
[0074] Preferably, the mass ratio of the first product to the cured resin is 1:(0.5-2).
[0075] Preferably, in step S2, the heating temperature of the second carbonization treatment is 1200-1500°C, and the holding time is 1-10h. Exemplarily, the heating temperature of the second carbonization treatment is any value in 1200°C, 1250°C, 1300°C, 1350°C, 1400°C, 1450°C, 1500°C, or any value in the range of any two of the above values, and the holding time of the second carbonization treatment is any value in 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, or any value in the range of any two of the above values.
[0076] Preferably, the heating rate of the second carbonization treatment is 0.1-10°C / min. Exemplarily, the heating rate of the second carbonization treatment is any value among 0.1°C / min, 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min or any value within the range of any two of the above values.
[0077] During the second carbonization process, CO, CO2 and alkane gases will be generated during the carbonization of the cured resin. Among them, CO and CO2 have pore-forming functions, which make the chitosan-based hard carbon material produce an open-pore structure. As the carbonization proceeds, the chitosan-based carbon undergoes C rearrangement and a closed-pore structure, which can increase the degree of graphitization of the chitosan-based hard carbon material, thereby increasing the capacity of the chitosan-based hard carbon material. The generated alkane gases can be deposited on the surface of the chitosan-based hard carbon material to form a carbon layer, thereby reducing the specific surface area of the hard carbon material, reducing the side reactions between the electrolyte and the hard carbon surface, and effectively improving the primary effect.
[0078] In step S3, the second product is sieved to remove resin hard carbon and chitosan lamellae hard carbon with large particles. In the embodiment of the present invention, the mesh number of the sieve is preferably 100 mesh.
[0079] The purpose of pickling in step S3 is to remove impurities generated during the production process. In an embodiment of the present invention, the pickling in step S3 is: placing the third product in an acidic solution with a molar concentration of 0.5 to 2M, stirring at a temperature of 10 to 30°C for 10 to 14 hours, filtering, and washing with water until neutral. The acidic solution is, for example, one or more of a hydrochloric acid solution, a nitric acid solution, and a sulfuric acid solution. The dosage ratio of the third product to the acidic solution is, for example, (10 to 50) g: (100 to 500) mL.
[0080] In a third aspect, the present invention provides a negative electrode plate, which includes the hard carbon material mentioned above, and / or the hard carbon material prepared by the above preparation method.
[0081] In an embodiment of the present invention, the negative electrode plate includes a negative electrode current collector and a negative electrode active material layer disposed on at least one side surface of the negative electrode current collector.
[0082] In an embodiment of the present invention, the negative electrode active material layer includes a negative electrode active material, and the negative electrode active material includes the hard carbon material.
[0083] In an embodiment of the present invention, the negative electrode active material layer further includes at least one of a conductive agent and a binder. The present application does not particularly limit the types of conductive agents and binders in the negative electrode active material layer, as long as the purpose of the present application can be achieved. As an example, the conductive agent in the negative electrode active material layer can be selected from at least one of carbon black, SuperP (SP), acetylene black, Ketjen black, carbon nanotubes, graphene, and carbon nanofibers. As an example, the binder in the negative electrode active material layer can be selected from at least one of carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), polymethacrylic acid (PMAA), carboxymethyl chitosan (CMCS), and sodium alginate (SA).
[0084] The present application has no particular restrictions on the mass ratio of the negative electrode active material, the conductive agent and the binder in the negative electrode active material layer, as long as the purpose of the present application can be achieved. For example, the mass percentage of each component in the negative electrode active material layer is: 70% to 98% of the negative electrode active material, 1% to 15% of the conductive agent, and 1% to 15% of the binder.
[0085] The present application has no particular restrictions on the preparation method of the negative electrode sheet, as long as the purpose of the present application can be achieved. Exemplarily, the preparation method of the negative electrode sheet includes: mixing the negative electrode active material, the conductive agent, the binder and the solvent to obtain the negative electrode slurry; coating the negative electrode slurry on the negative electrode collector, drying, cold pressing and cutting to obtain the negative electrode sheet.
[0086] In a fourth aspect, the present invention provides a sodium ion battery comprising the above-mentioned negative electrode plate.
[0087] In an embodiment of the present invention, the structure of the sodium ion battery includes but is not limited to button batteries, soft-pack batteries, cylindrical batteries, and the like.
[0088] The present application has no particular restrictions on the positive electrode sheet, separator, and electrolyte in the battery, and those skilled in the art can select them according to actual needs as long as the purpose of the present application can be achieved.
[0089] In the embodiment of the present invention, the morphology and microstructure analysis of the hard carbon material sample is obtained by scanning electron microscopy (SEM).
[0090] The reagents, instruments or materials used in the present invention can be obtained through commercial channels.
[0091] The present invention will be further described below in conjunction with embodiments:
[0092] Example 1
[0093] (1) Pretreatment of chitin: 25 g chitin powder (passed through a 80-mesh sieve) was dispersed in 200 mL of 5% NaOH solution, stirred at 60 °C for 6 h, filtered, washed to neutrality, and dried. Subsequently, 200 mL of 1 M HCl solution was added, stirred at room temperature for 12 h, then filtered, washed to neutrality, and dried for later use.
[0094] (2) Carbonization of chitosan: The pretreated chitosan was placed in a porcelain boat, and argon gas was introduced into a tubular furnace at a flow rate of 60 mL / min. The tubular furnace was heated to 700°C (the first carbonization treatment temperature) at a heating rate of 2°C / min. After being kept at this temperature for 5 h, the chitosan was taken out and ball-milled to obtain a first product with a particle size of less than 45 μm.
[0095] (3) Hard carbon pore formation and carbon coating: The first product was mixed with a highly cured resin (which was a coating agent, with a degree of cure of 98%, a particle size of 2 to 5 mm, and a carbon fixation rate of 50%) in a mass ratio of 1:1 to obtain a mixture. The mixture was then placed in a porcelain boat, and argon gas was introduced into a tubular furnace at a flow rate of 60 mL / min. The tubular furnace was heated to 1300°C (the second carbonization treatment temperature) at a heating rate of 5°C / min, and the mixture was taken out after being kept at this temperature for 5 h to obtain the second product.
[0096] (4) Screening and acid washing: The second product was screened (100 mesh screen) to remove resin hard carbon and chitin lamellar hard carbon with large particles, and then the third product was obtained. The third product was acid washed with 1 M HCl (stirred at room temperature for 12 hours), washed to neutrality, and then ball milled to obtain a new lamellar structure hard carbon material for sodium ion batteries. The particle size of the lamellar structure hard carbon material is 5 to 10 μm, and the thickness of the carbon layer is 2 to 5 nm.
[0097] Depend on Figure 1 It can be clearly seen that the material presents a layered structure.
[0098] Depend on Figure 2 It can be clearly seen that the single-layer lamellae of the lamellae structure are composed of orderly arranged chitosan carbon nanofibers, and the surface is dense.
[0099] Depend on Figure 3 It can be clearly seen that the chitosan-based hard carbon material has several closed-pore structures (the positions marked with red circles are all closed-pore structures).
[0100] Example 2a
[0101] The difference from Example 1 is that in step (3), the first product and the highly cured resin are mixed at a mass ratio of 1:0.5. The other conditions remain unchanged.
[0102] Example 2b
[0103] The difference from Example 1 is that in step (3), the first product and the highly cured resin are mixed in a mass ratio of 1:2. The other conditions remain unchanged.
[0104] Example 2c
[0105] The difference from Example 1 is that in step (3), the first product and the highly cured resin are mixed at a mass ratio of 1:0.25. The other conditions remain unchanged.
[0106] Example 2d
[0107] The difference from Example 1 is that in step (3), the first product and the highly cured resin are mixed in a mass ratio of 1:3. The other conditions remain unchanged.
[0108] Example 3a
[0109] The difference from Example 1 is that in step (3), the second carbonization treatment temperature is 1200° C. and the temperature is kept for 10 hours. The other conditions remain unchanged.
[0110] Example 3b
[0111] The difference from Example 1 is that in step (3), the second carbonization treatment temperature is 1500° C. and the temperature is maintained for 1 hour. The other conditions remain unchanged.
[0112] Example 4a
[0113] The difference from Example 1 is that in step (2), the first carbonization treatment temperature is 500° C. and the temperature is kept for 10 hours. The other conditions remain unchanged.
[0114] Example 4b
[0115] The difference from Example 1 is that in step (2), the first carbonization treatment temperature is 900° C. and the temperature is maintained for 1 hour. The other conditions remain unchanged.
[0116] Comparative Example 1
[0117] Compared with Example 1, this comparative example does not include the steps of hard carbon pore formation and carbon layer coating, and the specific preparation steps are as follows:
[0118] (1) Pretreatment of chitin: 25 g chitin powder (passed through a 80-mesh sieve) was dispersed in 200 mL of 5% NaOH solution, stirred at 60 °C for 6 h, filtered, washed to neutrality, and dried. Subsequently, 200 mL of 1 M HCl solution was added, stirred at room temperature for 12 h, then filtered, washed to neutrality, and dried for later use.
[0119] (2) Carbonization of chitin: The pretreated chitin was placed in a porcelain boat, and argon gas was introduced into a tubular furnace at a flow rate of 60 mL / min. The tubular furnace was heated to 700°C at a heating rate of 2°C / min and kept at this temperature for 5 h before being taken out to obtain the first product.
[0120] (3) Screening and acid washing: The first product is screened (100 mesh screen) to remove the larger particles of chitin lamellar hard carbon, and then the second product is obtained. The second product is acid washed with 1 M HCl until neutral, and then ball milled to obtain a new lamellar structure hard carbon material for sodium ion batteries.
[0121] Depend on Figure 4 It can be clearly seen that there are a large number of pore structures on the surface of the layer structure.
[0122] Comparative Example 2
[0123] Compared with Example 1, the coating agent of this comparative example is changed from highly cured resin to methane, and the specific preparation steps are as follows:
[0124] (1) Pretreatment of chitin: 25 g chitin powder (passed through a 80-mesh sieve) was dispersed in 200 mL of 5% NaOH solution, stirred at 60 °C for 6 h, filtered, washed to neutrality, and dried. Subsequently, 200 mL of 1 M HCl solution was added, stirred at room temperature for 12 h, then filtered, washed to neutrality, and dried for later use.
[0125] (2) Carbonization of chitin: The pretreated chitin was placed in a porcelain boat, and argon gas was introduced into a tubular furnace at a flow rate of 60 mL / min. The tubular furnace was heated to 700°C at a heating rate of 2°C / min and kept at this temperature for 5 h before being taken out to obtain the first product.
[0126] (3) The first product was fed into a CVD reactor (inner diameter 7 mm), and the temperature was raised to 700°C at a rate of 5°C / min under a nitrogen atmosphere, with a nitrogen flow rate of 100 ml / min, and the temperature was kept constant for 20 minutes; then the atmosphere was changed to methane, with a methane gas flow rate of 100 ml / min, a heating rate of 5°C / min, a temperature of 700°C, and a reaction time of 1 hour; then the atmosphere was changed to nitrogen and the temperature was lowered to room temperature to obtain the second product.
[0127] (4) The second product is screened (100 mesh screen) to obtain the second product. The second product is acid-washed with 1 M HCl until neutral, and then ball-milled to obtain a new lamellar hard carbon material for sodium ion batteries.
[0128] Performance Test 1
[0129] The specific surface area of the hard carbon materials prepared in the above examples and comparative examples was determined, and the specific surface area of the samples was determined using the nitrogen desorption curve. In this experiment, the samples were tested using a QUADRASORB-EVO specific surface area analyzer. The degassing conditions were 120°C, 12 h, and the test temperature was 77 K. The multi-point adsorption Brunauer-Emmett-Teller (BET) method was used to calculate the specific surface area.
[0130] The closed porosity and pore size of the hard carbon materials prepared in the above examples and comparative examples were measured. The closed porosity was measured by the helium true density method, and the pore size was obtained by SAXS simulation fitting.
[0131] The test results are shown in Table 1.
[0132] Table 1 Specific surface area, closed porosity and pore size test results
[0133]
[0134] The results show that compared with Comparative Example 1, the alkane gas generated during the carbonization process of the cured resin in Examples 1 to 4 can cover a carbon layer on the surface of the chitosan lamellae carbon, which can significantly reduce the specific surface area of the hard carbon material.
[0135] Performance Test 2
[0136] 1. Preparation of sodium ion batteries
[0137] (1) The negative electrode materials prepared in the above embodiments and comparative examples are used as negative electrode active materials, carbon black is used as a conductive agent, and carboxymethyl cellulose (CMC) is used as a binder, and the mass ratio is negative electrode active material: conductive agent: binder = 8:1:1. The materials are mixed according to the above ratio to obtain negative electrode slurry, and the negative electrode sheet is further prepared by conventional technology.
[0138] (2) Provide a sodium metal sheet as the positive electrode.
[0139] (3) A glass fiber diaphragm is provided as an isolation membrane.
[0140] (4) Providing an electrolyte solution, wherein the electrolyte solution is prepared by dissolving 1.0 mol / L NaPF6 in diethylene glycol dimethyl ether.
[0141] (5) Assemble the negative electrode sheet, the separator, and the positive electrode sheet in order, soak them with electrolyte, and assemble them into a CR2032 button battery in an argon glove box.
[0142] 2. Test the battery's first discharge capacity, first charge capacity and first coulomb efficiency
[0143] First discharge capacity, first charge capacity, first coulomb efficiency test: Use Land battery test system, at 25℃, discharge at 0.1C constant current to 0V, record the discharge capacity at this time as the first discharge capacity; charge at 0.1C constant current to 2V, record the charge capacity at this time as the first charge capacity; first coulomb efficiency = first charge capacity / first discharge capacity × 100%.
[0144] The test results are as follows:
[0145] Table 2 Button half-cell performance test results
[0146]
[0147] As can be seen from Table 1, the button-type half-cells of Examples 1 to 4 all have relatively high initial reversible capacities, all exceeding 300 mAh / g.
[0148] It is worth noting that the first coulombic efficiency of Examples 1 to 4 is significantly improved compared with that of Comparative Example 1. The first coulombic efficiency of Comparative Example 1 is only 50.4%, while that of Examples 1 to 4 is greater than 85%. It can be seen that the alkane gas generated by the resin after the curing of the embodiment in the carbonization process can cover a carbon layer on the surface of the chitosan sheet carbon, effectively reducing the specific surface area and reducing the side reaction between the electrolyte and the hard carbon surface, thereby effectively improving the first coulombic efficiency.
[0149] In Comparative Example 2, since the coating agent is changed to methane, the coating agent cannot form pores in the chitosan-based hard carbon material, and the carbon coated by methane deposition is amorphous carbon, it exhibits lower first discharge capacity, first charge capacity and first coulombic efficiency.
[0150] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A hard carbon material having a lamellar structure, characterized in that: The hard carbon material comprises a hard carbon matrix and a carbon layer coated on the surface of the hard carbon matrix; The hard carbon matrix comprises a chitosan-based hard carbon material, wherein the chitosan-based hard carbon material has a stacked layer structure and a closed-pore structure; The method for preparing the hard carbon material comprises the following steps: S1, in an inert gas atmosphere, performing a first carbonization treatment on chitosan, and obtaining a hard carbon matrix after a first ball milling treatment; the heating temperature of the first carbonization treatment is 500-900° C., and the holding time is 1-10 h; S2, mixing the hard carbon matrix and the cured resin to obtain a mixture; the degree of curing of the cured resin is not less than 95%; In an inert gas atmosphere, the mixture is subjected to a second carbonization treatment to obtain hard carbon coated with a carbon layer; the heating temperature of the second carbonization treatment is 1200-1500° C., and the holding time is 1-10 h; S3, sieving the hard carbon coated with the carbon layer to obtain a third product; The third product is acid-washed and subjected to a second ball milling process to obtain a hard carbon material.
2. The hard carbon material according to claim 1, characterized in that The closed porosity of the hard carbon material is 5% to 30%; The number of layers of the lamellar structure is ≥2; The number of the closed-cell structures is ≥ 1; The pore size of the closed-cell structure is 0.1 to 3 nm; The specific surface area of the hard carbon material is 8 to 15 m 2 / g.
3. The hard carbon material according to claim 1 or 2, characterized in that The thickness of the carbon layer is 2 to 5 nm; The particle size of the hard carbon material is 5 to 10 μm.
4. The method for preparing the hard carbon material according to any one of claims 1 to 3, characterized in that: The steps include: S1, in an inert gas atmosphere, performing a first carbonization treatment on chitosan, and obtaining a hard carbon matrix after a first ball milling treatment; the heating temperature of the first carbonization treatment is 500-900° C., and the holding time is 1-10 h; S2, mixing the hard carbon matrix and the cured resin to obtain a mixture; the degree of curing of the cured resin is not less than 95%; In an inert gas atmosphere, the mixture is subjected to a second carbonization treatment to obtain hard carbon coated with a carbon layer; the heating temperature of the second carbonization treatment is 1200-1500° C., and the holding time is 1-10 h; S3, sieving the hard carbon coated with the carbon layer to obtain a third product; The third product is acid-washed and subjected to a second ball milling process to obtain a hard carbon material.
5. The preparation method according to claim 4, characterized in that: In step S1, the heating rate of the first carbonization treatment is 0.1-10°C / min.
6. The preparation method according to claim 4, characterized in that: In step S2, the particle size of the cured resin is not less than 2 mm, and the carbon fixation rate is not less than 40%.
7. The preparation method according to claim 4, characterized in that: The mass ratio of the hard carbon matrix to the cured resin is 1:(0.25-3).
8. The preparation method according to claim 4, characterized in that: In step S2, the heating rate of the second carbonization treatment is 0.1-10°C / min.
9. A negative electrode plate, characterized in that: The negative electrode plate comprises the hard carbon material according to any one of claims 1 to 3, and / or the hard carbon material prepared by the preparation method according to any one of claims 4 to 8.
10. A sodium ion battery, characterized in that: The sodium ion battery comprises the negative electrode sheet according to claim 9.
Citation Information
Patent Citations
Sodium-ion battery core-shell structure bagasse hard carbon-based negative electrode material and preparation method thereof
CN116332152A
High-capacity compact hard carbon negative electrode material and preparation method and application thereof
CN116722139A
Negative electrode material, secondary battery and electric equipment
CN117613265A
